Science Communication Skills For Journalists A Resource Book for Universities In Africa - Wendo, Charles (CABI, 2022)
This book has an introduction and 22 other chapters that cover science communication skills. The editor has detailed knowledge of the field and consultation with leading editors and journalists in the region. It provides hands-on guidance together with examples, learning activities, graded and ungraded quizzes to facilitate learning. The content has been tried and tested by lecturers at two universities in Nigeria and Uganda, who used it to successfully train thousands of students in science communication. Each chapter carries hands-on advice on the practice of science journalism, with learning activities to deepen the learner's understanding of the topic. The book also includes five academic systematic review papers, written by university faculty, that that identify, review and synthesize available literature and experiences on science journalism and communication issues in the region. It also includes a case study detailing the experience of Uganda's Makerere University in introducing science journalism and communication into their undergraduate and post-graduate curricula.